Isolation and characterization of fungal pathogen associated with oil palm black base rot disease - Latif, Nurnashirah (2016)
Elaeis guineensis Jacq. is a perennial monocotyledonous crop that has been contributing to Malaysia’s economy generously. However there are some culprit diseases causing yield reduction and lifespan of the palm. Recently symptoms of a disease caused by a black fungus, which colonized on matured palm bole and trunk tissues were detected in Malaysia. This disease exhibits symptoms such as dry rot of the internal tissues at the base of the stem, upper roots and presence of black sclerotia attached to the vascular bundles in the pith. As the disease progresses, rotting starts on the bole of the palm and presence of hollow hole on the oldest trunk or base of oil palm can be observed. Hence, this project was designed with the objectives i) To isolate the fungal pathogen from BBR disease symptomatic oil palm tissues in the plantation and ii) To characterize and identify the isolated fungal pathogen based on morhological and molecular characteristics. In order to achieve these objectives, sampling of the symptomatic palm tissues from the plantations, followed by isolation of the fungal pathogen from the collected samples were carried out. Successfully isolated pure cultures were then subjected to cultural and morphological identification based on the demonstrated characteristics. In addition, molecular identification was also conducted on extracted fungal genomic DNA using ITS1 and ITS4 primer pairs for amplification purpose. Subsequently, PCR product obtained were subjected to sequencing and BLAST analysis against corresponding sequences in the GenBank database for species level identification. All the five isolates selected from ten isolates after cultural and morphological identification were identified as Ceratocystis paradoxa. As a conclusion, pathogenicity test conducted further confirmed C. paradoxa isolate as the causal fungal pathogen of black base rot (BBR) disease of oil palm.